Audio Visual Nutrition Education and Breakfast Habits in Children : Edukasi Gizi Berbasis Audio Visual dan Kebiasaan Sarapan Pada Anak - Oematan, Gustaf; Oematan, Grouse; Mege, Stacia R (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Breakfast is very important for the body. The right breakfast can provide the energy and important nutrients needed by children. The purpose of this service activity is to increase children's knowledge about nutrition and the importance of breakfast. This educational activity is carried out using audio-visual media in the form of animated videos. The results of the service showed an increase in students' knowledge before (pre test 4%) and after (post test 76.3%) educational activities were carried out. Abstrak Sarapan sangat penting bagi tubuh. Sarapan yang tepat dapat memberikan energi dan nutrisi penting yang dibutuhkan oleh anak. Tujuan kegiatan pengabdian ini adalah untuk meningkatkan pengetahuan anak mengenai gizi dan pentingnya sarapan. Kegiatan edukasi ini dilakukan menggunakan media audio visual dalam bentuk video animasi. Hasil pengabdian menunjukkan adanya peningkatan pengetahuan siswa sebelum (pre test 4%) dan setelah (post test 76,3%) kegiatan edukasi dilakukan.